Experiments on new polymer based mortars filled with FRP waste recyclates - a quantitative analysis - Ribeiro, M.C.S. (2014)
Glass fibre-reinforced plastics (GFRP) have been considered inherently difficult to recycle due to both: cross-linked nature of thermoset resins, which cannot be remolded, and complex composition of the composite itself. Presently, most of the GFRP waste is landfilled leading to negative environmental impacts and supplementary added costs. With an increasing awareness of environmental matters and the subsequent desire to save resources, recycling would convert an expensive waste disposal into a profitable reusable material. In this study, efforts were made in order to recycle grinded GFRP waste, proceeding from pultrusion production scrap, into new and sustainable composite materials. For this purpose, GFRP waste recyclates, were incorporated into polyester based mortars as fine aggregate and filler replacements at different load contents and particle size distributions. Potential recycling solution was assessed by mechanical behaviour of resultant GFRP waste modified polymer mortars. Results revealed that GFRP waste filled polymer mortars present improved flexural and compressive behaviour over unmodified polyester based mortars, thus indicating the feasibility of the waste reuse in polymer mortars and concrete. © 2011, Advanced Engineering Solutions.